Performance Evaluation of Maintenance Management Strategy Using Malcolm Baldrige Criteria - Muzayyanah Jabani; Ahmad Syawal Senong Pakata; Erwin Erwin (Hasanuddin Economics and Business Review, 2024)
This study aims to analyze the Maintenance Management strategy at PT Sumber Graha Sejahtera Luwu Branch by measuring Malcom Baldrige. Data collection techniques were carried out using questionnaires, interviews with the Maintenance Initiative Management Team, and data collection in the form of various internal company information used in the implementation of Maintenance Management initiatives. Data analysis using descriptive analysis and percentage analysis. The company's total score is based on the MBCfPE 2012 world class performance framework. The results show that the total score is obtained PT. Sumber Graha Sejahtera Luwu Branch for all MBNQA categories based on the results of the questionnaire is 724 or 72% of the maximum score of 1000. This means that for the performance assessment of PT. Sumber Graha Sejahtera Luwu Branch based on MBNQA, PT. Sumber Graha Sejahtera Luwu Branch won the title of Exellent and is included in the category Industry Leaders (point scale 676–775). Industry Leaders PT. Sumber Graha Sejahtera Luwu Branch is in a very good position.